Study on Double Pressure Funnels and Gas-Liquid Two-Way Mass Transfer after Fracturing in Shale Gas Reservoirs. (13th December 2022) - Lu, Zhiwei; Li, Xizhe; Liang, Xing; Hao, Youzhi
Abstract : Well shut-in and drainage after shale gas fracturing are important factors affecting the productivity. Due to the imperfect optimization method of shale gas flowback, there has been no clear explanation for the problems such as "formulation of reasonable well shut-in time" and "less fracturing fluid flowback but high-gas production phenomenon" during shale gas drainage. In this paper, the double pressure funnels (one funnel is formed during fracturing by pressure difference from wellbore to formation, and two funnels are formed during flowback by pressure difference from fracture to formation and from fracture to wellbore) and gas-liquid two-way mass transfer (gas transfer by diffusion and liquid transfer by pressure difference) in shale gas drainage are investigated by calculating the pressure distribution after fracturing shale gas wells. The discrete numerical simulation by using unstructured PEBI grid is conducted, and the result is as follows: when shale gas well is shut-in for 20 days and produce for 1 year, the daily gas production corresponding to fracturing fluid flowback rates of 20%, 10%, and 5% are 47700 m 3, 5800 m 3, and 72700 m 3, respectively. The investigation of double pressure funnels and gas-liquid two-way mass transfer explains clearly the phenomenon "less fracturing fluid flowback but high-gas production." Meanwhile, the two conditions for optimizing the well shut-in time after fracturing are presented. That is, as for the studied case, the moving speed of the pressure boundary line should be less than 0.1 m/d, and the water-gas ratio near the fracture should be less than 1 / d with time. Consequently, the reasonable well shut-in time is optimized to be 20-25 days. The findings in this work are of benefit to enrich the flowback theory of shale gas after fracturing and provide a theoretical basis for the optimization technology of shale gas drainage after fracturing.